Associations between red blood cell variants and malaria among children and adults from three areas of Uganda: a prospective cohort study - Kakande, Elijah; Greenhouse, Bryan; Bajunirwe, Francis; Drakeley, Chris; Nankabirwa, Joaniter I.; Walakira, Andrew; Nsobya, Samuel L.; Katureebe, Agaba; Rek, John; Arinaitwe, Emmanuel; Rosenthal, Philip J.; Kamya, Moses R.; et al. (Malaria Journal, 2020)
Background: Multiple red blood cell (RBC) variants appear to offer protection against the most severe forms of Plasmodium falciparum malaria. Associations between these variants and uncomplicated malaria are less clear. Methods: Data from a longitudinal cohort study conducted in 3 sub-counties in Uganda was used to quantify associations between three red blood cell variants Hb [AA, AS, S (rs334)], alpha thalassaemia 3.7 kb deletion, and glucose- 6-phosphate dehydrogenase deficiency A—(G6PD 202A genotype) and malaria incidence, parasite prevalence, parasite density (a measure of anti-parasite immunity) and body temperature adjusted for parasite density (a measure of anti-disease immunity). All analyses were adjusted for age, average household entomological inoculation rate, and study site. Results for all variants were compared to those for wild type genotypes. Results: In children, HbAS was associated, compared to wild type, with a lower incidence of malaria (IRR = 0.78, 95% CI 0.66–0.92, p = 0.003), lower parasite density upon infection (PR = 0.66, 95% CI 0.51–0.85, p = 0.001), and lower body temperature for any given parasite density (− 0.13 ℃, 95% CI − 0.21, − 0.05, p = 0.002). In children, HbSS was associated with a lower incidence of malaria (IRR = 0.17, 95% CI 0.04–0.71, p = 0.02) and lower parasite density upon infection (PR = 0.31, 95% CI 0.18–0.54, p < 0.001). α−/αα thalassaemia, was associated with higher parasite prevalence in both children and adults (RR = 1.23, 95% CI 1.06–1.43, p = 0.008 and RR = 1.52, 95% CI 1.04–2.23, p = 0.03, respectively). G6PD deficiency was associated with lower body temperature for any given parasite density only among male hemizygote children (− 0.19 ℃, 95% CI − 0.31, − 0.06, p = 0.003). Conclusion: RBC variants were associated with non-severe malaria outcomes. Elucidation of the mechanisms by which they confer protection will improve understanding of genetic protection against malaria.
Keywords: Red blood cell variants; Erythrocyte; Malaria; Plasmodium; Sickle hemoglobin; Thalassemia